Mobility and shape adaptation of neutrophil in the microchannel flow. (May 2017) - Czerwinska, Justyna; Pumpurus, Lauris; Rieger, Michael; Uehlinger, Dominik; Nita, Izabela; Blank, Fabian
Abstract: This paper presents motion of neutrophil in a confined environment. Many experimental and theoretical studies were performed to show mechanics and basic principles of the white blood cell motion. However, they were mostly performed on flat plates without boundaries. More realistic model of flow in the capillaries based on confinement, curvature and adequate dimensions is applied in our experiments. These conditions lead to cell motion with deformability and three-dimensional character of that movement. Neutrophils are important cells for human immune system. Their motion and attachment often influence several diseases and immune response. Hence, studies focus on that particular cell type. We have shown that deformability of the cell influences its velocity. Cells actively participate in the flow using the shear gradient to advance control motion. The observed neutrophil velocity was from 1 up to 100 μ m / s .